2014
DOI: 10.1007/s12040-014-0437-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil heat flux and day time surface energy balance closure at astronomical observatory, Thiruvananthapuram, south Kerala

Abstract: Soil heat flux is an important input component of surface energy balance. Estimates of soil heat flux were made in the year 2008 using soil temperature data at Astronomical Observatory, Thiruvananthapuram, south Kerala. Hourly values of soil heat flux from 00 to 24 LST are presented for selected days typical of the winter, pre-monsoon, SW monsoon and NE monsoon seasons. The diurnal variation is characterized by a cross-over from negative to positive values at 0700 h, occurrence of maximum around noon and retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Though the estimation of CCM was worse than the plate calorimetric method, CCM was better than FR on rain-free days, which was in good agreement with what Tyagi and Satyanarayana (2010) reported, i.e., the variation of G 0 from CCM was more reasonable than that from FR. Gao (2005) found that G 0 of CCM was more reliable than G 0 of the harmonic model by improving energy budget closure from 0.7 to 0.9 in Tibetan shortgrass prairie, while Roxy et al (2014) confirmed it as well.…”
Section: Conduction and Convection Modelmentioning
confidence: 89%
See 2 more Smart Citations
“…Though the estimation of CCM was worse than the plate calorimetric method, CCM was better than FR on rain-free days, which was in good agreement with what Tyagi and Satyanarayana (2010) reported, i.e., the variation of G 0 from CCM was more reasonable than that from FR. Gao (2005) found that G 0 of CCM was more reliable than G 0 of the harmonic model by improving energy budget closure from 0.7 to 0.9 in Tibetan shortgrass prairie, while Roxy et al (2014) confirmed it as well.…”
Section: Conduction and Convection Modelmentioning
confidence: 89%
“…Accurate determination of ground soil heat flux, G 0 , is required to evaluate surface energy balance (de Silans et al 1997;Heusinkveld et al 2004;Roxy et al 2014), to estimate soil evaporation (Kampf et al 2005;Heitman et al 2010;Yao et al 2013), and to describe water and vapor transformation processes in vadose zone (Yamanaka et al 1997;Saito et al 2006;Bittelli et al 2008;Wang et al 2011aWang et al , 2011bZhang et al 2015). However, measurement of G 0 has still been a challenging task for researchers till now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sauer and Horton (2005) summarized the advantages and disadvantages of the calorimetric, gradient, and combination methods, but point out that the gradient method is sensitive to λ, which can be difficult to estimate accurately for field conditions. Furthermore, these methods do not account for convection of heat by water movement (Evett et al, 2012a;Roxy et al, 2014). Evett et al (2012a) show that λ can be estimated for field conditions using a nonlinear fitting procedure of soil temperature measurements at successive depths and times.…”
Section: Calorimetric Methods For Gmentioning
confidence: 99%
“…Available net radiation is the balance between incoming and outgoing radiation which is the main source of energy in the earth system. The balance of energy at the earth's surface is closely associated with the overlying atmospheric boundary layer (Roxy et al, 2014). The total available energy and partitioning of it into different components such as sensible heat (h), latent heat (LE) and soil heat fluxes (G) influences the production of the crop very strongly.…”
Section: Introductionmentioning
confidence: 99%